2013
DOI: 10.1159/000361011
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Cross-Resistance to Aminoglycosides in Fluoroquinolone-Resistant Escherichia coli Clinical Isolates

Abstract: Background: Multidrug-resistant Escherichia coli, especially a lineage of O25b:H4-ST131, has increased and spread worldwide. The surveillance of cross-resistance of E. coli is necessary. Methods: Cross-resistance to fluoroquinolones (FQs) and aminoglycosides (AGs) was examined in E. coli isolated in Hokkaido Prefecture, Japan, between 2008 and 2009. Results: Gentamicin (GEN) resistance was more common in FQ-resistant isolates (30/112 strains; 26.8%) than in FQ-susceptible isolates (2/100 strains; 2%). The freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Resistance to ciprofloxacin, amikacin and tobramycin was significantly more prevalent in the LTC applicants, with the amikacin and tobramycin resistance being caused mainly by carriage of the aac(6')-Ib gene linked to bla CTX-M-15 carriage. In agreement, it was also shown that ciprofloxacin resistance is associated with aminoglycoside resistance in ESBL-producer and non-ESBL producer E. coli [46]. …”
Section: Discussionmentioning
confidence: 64%
“…Resistance to ciprofloxacin, amikacin and tobramycin was significantly more prevalent in the LTC applicants, with the amikacin and tobramycin resistance being caused mainly by carriage of the aac(6')-Ib gene linked to bla CTX-M-15 carriage. In agreement, it was also shown that ciprofloxacin resistance is associated with aminoglycoside resistance in ESBL-producer and non-ESBL producer E. coli [46]. …”
Section: Discussionmentioning
confidence: 64%
“…E. coli ATCC 25922 was used as a reference. The MIC values for CIP, cefpodoxime, cefepime, and gentamicin were obtained from previous studies of E. coli isolates from 2008 and 2009 (4,6,43). MICs for ceftazidime (GSK Japan, Tokyo, Japan), imipenem (MSD, Tokyo, Japan), amikacin (Wako Pure Chemical, Osaka, Japan), and fosfomycin (Meiji Seika Pharma, Tokyo, Japan) were also determined using the agar plate dilution method.…”
Section: Methodsmentioning
confidence: 99%
“…Multidrug-resistant (MDR) isolates are resistant to at least three antibiotics ( 10 ). The evaluation of epidemiological data concerning MDR E. coli and K. pneumoniae in different parts of the world indicates their increased prevalence with noticeable varieties in many countries ( 11 - 13 ). These differences necessitate regional surveys about their resistance patterns and risk factors.…”
Section: Introductionmentioning
confidence: 99%